Seasonal abundance of Acyrthosiphon pisum (Harris) (Homoptera: Aphididae) and Therioaphis trifolii (Monell) (Homoptera: Gallaphididae) on lucerne in Central Greece - Lykouressis, D. P.; Polatsidis CH. Ρ. (ENTOMOLOGIA HELLENICA, 1990)
Acyrthosiphon pisum (Harris) and Therioaphis trifolii (Monell) were the most abundant aphid species on lucerne at Kopais, Co. Boiotia in central Greece from April 1984 to November 1986. Population fluctuations for A. pisum showed two peaks, the first during April-May and the second in November. Low numbers or zero were found during summer and till mid October as well as during winter and March. The abundance of this species during the year agrees generally with the effects of prevailing temperatures in the region on aphid development and reproduction. T. trifolii also showed two population peaks but at different periods. The first occurred in July and the second from mid September to mid October. The first peak was higher than the second. The sharp decline in population densities that occurred in early August and lasted till mid September is not accounted for by adverse climatic conditions, but natural enemies and/or other limiting factors are possibly responsible for that population reduction. Numbers were zero from December till March, while they kept at low levels during the rest of spring and part of June as well as from mid October till the end of November.